Application of a method to assess hydraulic heritage as regards diversion dams in the Júcar river basin. A decision-making tool - Sandra MAYORDOMO MAYA; Miguel ANTEQUERA FERNΑNDEZ; Jorge HERMOSILLA PLA (European Journal of Geography)
The Mediterranean area is distinctive for its acute water deficit. This scarcity of water has led to the gradual construction of historical, sustainable irrigation systems of significant cultural and scenic value. It is essential to identify and evaluate these systems and their hydraulic assets in order to come up with proposals aimed at managing and conserving them. In this study, a method is used to assess the hydraulic heritage in ninety three (93) weirs or diversion dams located in the eastern Iberian Peninsula, following a proposal by the Júcar River Basin Authority (Confederación Hidrográfica del Júcar). It is a quantitative method using various criteria that also takes into account the participation of social agents. Its application has enabled these water-damming works to be classified according to the interest in them in terms of heritage. A public administration’s use of the method confirms that it is an effective evaluation instrument to prioritise activities involving management and appreciation of these assets.